Development of sample collection methods and preliminary identifications of aphid salivary proteins - Lamabadusuriya, Manuja R. (Kansas State University, 2009)
The study of aphid salivary secretome has practical importance on understanding interactions of aphids and their host plants. Around 250 species of aphids out of the identified 4000 aphid species are considered as serious pests. The experiments were performed with pea aphids (Acyrthosiphon pisum) that were feeding on bean plants (Vivia fabe). Pea aphids feed on plant phloem sap by probing their stylet into the sieve elements of the plant and secreting saliva for external digestion. In order to collect aphid salivary proteins from the secreted saliva, small scale and large scale sample collection methods were carried out. The small scale sample method was performed in microfluidic devices using 10-25 aphids. Aphids were able to feed on the artificial diet by probing through a stretched ParafilmTM and survived for 2-3 days in the microfluidic devices. The experiments proved that the aphid survival and feeding rate could be improved with the factors such as ventilation, light intensity and increasing diet volume. However it was difficult to collect sufficient amounts of aphid saliva for detection using small scale devices. The large scale sample collection method was performed by feeding 8000 aphids in large screened chamber for 24/48h. The collected salivary samples after undergone a concentration process was capable of collecting detectable aphid salivary secretions. The experimental conditions were adjusted to obtain optimized HPLC separations. Finally, LC/MS/MS followed by peptide sequence database searching were able to identify potential aphid salivary proteins.
Keywords: Aphid salivary proteins; Collection method; Chemistry, Analytical (0486)